Creating a Virtuous Leviathan: The Party, Law, and Socialist Core Values. Issue 1 (28th February 2019) - LIN, Delia; TREVASKES, Susan
Abstract: In recent years, the Chinese Communist Party has declared that its governance must dominate over all aspects of law-making and enforcement, declaring that its leadership must be implemented across the entire process of governing the country in accordance with the law. Contemporaneous to this new way of thinking about the law-Party nexus is a propaganda push to integrate moral values into the law. This paper is about moralizing governance in the Xi Jinping era. It explores the ideology behind the promotion of this morals–law integration, focusing on the Socialist Core Values in the legal realm under the current Xi Jinping administration. We do so from two interrelated perspectives. The first examines the relationship between law and morality. Here, we argue that the Party's calls for a law–morality amalgam can be understood as a form of "pan-moralism." The second looks at the supremacy of Party rule, extending the theory of the "Leviathan" proposed by Thomas Hobbes to take into account the Party's morality push. This two-pronged argument enables us to assert that the Xi Jinping administration is creating a "virtuous Leviathan."